Evaluating Users’ Emotional Experience in Mobile Libraries: An Emotional Model Based on the Pleasure-Arousal-Dominance Emotion Model and the Five Factor Model - Zhao, Yang; Xie, Dan; Zhou, Ruoxin; Wang, Ning; Yang, Bin (Frontiers in Psychology, 2022)
As a part of user experience, user emotion has rarely been studied in mobile libraries. Specifically, with the proposed emotional model in combination with the Pleasure-Arousal-Dominance (PAD) Emotion Model and the Five Factor Model (FFM), we evaluate user emotions on the mobile library’s three IS features (i.e., user interface, interaction quality, and service environment). An experience procedure with three tasks has been designed to collect data. 50 participants were enrolled, and they were asked to fill in questionnaires right after the experience. The correlations among the PAD emotions were examined. Specifically, users have a low perception of pleasure (P), high perception of arousal (A), and low perception of dominance (D). However, these three emotional states were not always significantly correlated with each other. This study extends mobile library research by focusing on users’ emotional experience. Specifically, the detailed PAD emotions have been examined. This study provides a new approach for application developers and managers to evaluate the user experience of an application.